2022
DOI: 10.1111/jth.15788
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patients' experience and related qualitative outcomes in venous thromboembolism: A scoping review

Abstract: Background: Venous thromboembolism (VTE) is a prevalent disease with high morbidity and mortality. VTE has well-documented physical sequelae; however, the psychological and emotional impacts are seldom evaluated in randomized controlled trials. Objective:We conducted a scoping review of published qualitative studies aiming to understand the physical, psychological, and emotional impact of VTE as reflected from patients' perspectives. This scoping review is part of a larger initiative to develop a core outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 61 publications
0
9
0
1
Order By: Relevance
“…Clearly there is a lot that patients go through, following a VTE diagnosis and HMB would only add to this, particularly under the sub-theme of burden of anticoagulation , identified by the authors of this review. Clinicians should be mindful of this as it once again highlights the importance of trying to prevent HMB in the first place [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clearly there is a lot that patients go through, following a VTE diagnosis and HMB would only add to this, particularly under the sub-theme of burden of anticoagulation , identified by the authors of this review. Clinicians should be mindful of this as it once again highlights the importance of trying to prevent HMB in the first place [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, trials in VTE have focused most frequently (almost exclusively) on objective binary primary outcomes such as bleeding, recurrent VTE, and mortality. 17 19 Adding patient-reported outcome measures (PROMS) capturing QoL and/or functional outcomes to the primary outcome instead of using PROMS as a secondary outcome or merely an afterthought would broaden the scope of such trials, facilitating translation of the findings of a trial to daily clinical practice.…”
mentioning
confidence: 99%
“…A Canadian study identified seven major themes related to patients’ experiences with VTE: acute impacts (initial shock and physical symptoms), sustained psychological distress (fear of recurrence and death), loss of self (changing habits and taking decisions for the future), challenges of VTE treatment (anticoagulation and elastic compression stockings), balance of life changes, negative experience with the medical system (delays and diagnostic errors), and VTE in the context of other conditions. 4 …”
mentioning
confidence: 99%
“…Um estudo canadense levantou sete temas maiores relacionados à experiência do paciente com TEV: o impacto agudo (choque inicial e sintomas físicos), o sofrimento psicológico persistente (medo de recorrência e morte), a perda de si mesmo (mudanças de hábitos e tomada de decisões para o futuro), os desafios no tratamento do TEV (anticoagulação e meias de compressão elástica), o equilíbrio nas mudanças de vida, a experiência negativa com o sistema de saúde (atrasos e erros diagnósticos) e o TEV no contexto de outras doenças 4 .…”
unclassified